Assessment of the Validity of Carbon Ion Irradiation for C6 Gliomas in Rats - Yufeng Li; Lei Ta; QingFeng Wu; Hongyu Zhang; Yuan Xu; Lu Gan; Jianli Liu (Dose-Response)
Purpose Application of energy-spectrum computed tomography (CT) to assess specific efficacy of and response to carbon ion radiotherapy (CIRT) of C6 gliomas in rats. Methods After establishing C6 glioma rat models, 3 tumor-bearing rats were randomly selected as controls. The remaining were divided into 0 Gy, 1 Gy, and 2 Gy groups for CIRT. Energy-spectrum CT scans were performed, and brain tissues were collected for histopathology and western blot Test. Survival rates in each group were compared. Results The results demonstrated that tumors in the 1 Gy and 2 Gy groups decreased at different rates up to 14 days post-CIRT ( P < 0.05). Furthermore, compared to pre-CIRT measurements, the energy-spectrum parameters gradually increased in the 0 Gy group, while they decreased in the 2 Gy group. Post-CIRT, the Ki-67 proliferation index and the expression levels of vascu-larassociated proteins in tumor tissues were significantly reduced in the 1 and 2 Gy groups. Additionally, the survival times of tumor-bearing rats were prolonged after CIRT. Conclusions CIRT effectively restricts tumor cell growth and proliferation, leading to improved survival rates in rats with C6 gliomas. The use of energy-spectrum CT with immunohistochemistry for quantitative detection can actively support the effectiveness of carbon ion radiotherapy in inhibiting tumor proliferation.